The Influence of Media Facilities on Playing Geometrics on Early Childhood Numeracy Skills - Fatimatuzzuhroh Husniati (Fakultas Tarbiyah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aimed to determine the impact of Geometry Play Media on early childhood. The experimental group and the control group are used in this investigation. This quantitative research strategy uses an Experimental Design and a Nonequivalent Control Group Design. The population in this study was 30 children of TK ABA 31 Semarang; the samples in class A were 15 children, and the samples in class B were 15 children. This research will use a saturated sampling technique. Saturated sampling is done if there are fewer members of the population. Therefore, all members of the population are used as research samples. Techniques for gathering data include observation, documentation, and unstructured tests. This study's data analysis methodologies employed the normality test, homogeneity test, and hypothesis test. According to the independent sample t-test calculation, the significance value of the control class pretest is 0.001 < 0.05, and that of the experimental class pretest is 0.001 < 0.05. The significance value of the control class posttest is 0.000 < 0.05, and the value of the experimental class posttest is 0.000 < 0.05. As a result, the conclusion of the research conducted by researchers using Ho is rejected. In contrast, Ha is approved, indicating that the geometry media substantially influences the numeracy skills of TK ABA 31 students in Semarang.